2015
DOI: 10.3906/sag-1401-19
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome in multiple sclerosis

Abstract: IntroductionRestless legs syndrome (RLS) is a sleep disorder characterized by an urge to move the legs associated with uncomfortable paresthesias. Usually, the symptoms manifest in the evening or at night, when the patients take rest, and are relieved by walking or moving the legs (1). Diagnosis of RLS needs to involve the following clinical features: (a) uncomfortable and unpleasant sensations in the legs, (b) worsening of the symptoms during rest, (c) relief of the symptoms by movement, (d) exacerbation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…There were no cases considered appropriate from inclusion in the severe (21-30) or very severe (31-40) group. For the controls there was one mild case (0-10) and one moderate case (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Demographic Data Are Presented In Tablementioning
confidence: 99%
See 1 more Smart Citation
“…There were no cases considered appropriate from inclusion in the severe (21-30) or very severe (31-40) group. For the controls there was one mild case (0-10) and one moderate case (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Demographic Data Are Presented In Tablementioning
confidence: 99%
“…RLS patients declare worse global quality of life and important impairments of mental and general physical status compared to healthy individuals or to patients with other conditions (6). There are several diseases/conditions which are suggested to increase the prevalence of RLS: Renal failure (8), kidney transplantation (9), rheumatoid arthritis (10), fibromyalgia (11), lung transplantation (12), migraine (13), ankylosing spondylitis (14) or multiple sclerosis (15). In pregnancy, the prevalence of RLS is also high, but in contrast with the aforementioned conditions, it has a good prognosis, remitting in few weeks/months after delivery (16).…”
Section: Introductionmentioning
confidence: 99%
“…Also, NLR was evaluated in some central or systemic neurologic diseases including ischemic and hemorrhagic cerebrovascular diseases, myasthenia gravis and multiple sclerosis and was correlated with prognosis (29,30,31,32). In addition, some studies showed that RLS was more common in neurologic conditions in which the NLR was found increased (33,34,35).…”
Section: Discussionmentioning
confidence: 99%